Longitudinal shear in the tension flanges of composite concrete beams made continuous. (14th December 2021) - Kytölä, Ulla; Tulonen, Joonas; Laaksonen, Anssi
Abstract: In continuous concrete T‐beams, tension flange plays a remarkable role for the hogging moment capacity at the support area. When precast beams are connected as a continuous structure, longitudinal reinforcement is spread in the flange overhangs at the negative moment area of the continuity connection, which causes longitudinal shear in the tension flange's web‐flange junction. The level of reinforcement spreading influences the magnitude of in‐plane forces at the junction, which can cause the flanges to crack and eventually separate from the web. This separation must be prevented by providing transversal reinforcement in the flanges. Longitudinal shear between web and flange and the required transversal reinforcement are experimentally and computationally studied in cantilever composite T‐beams with the flange in tension. A comparison of the experimental and computational results revealed that longitudinal shear distribution in accordance with conventional beam theory does not always yield safe side results. Analyses made with a particularly drawn truss model and the modified compression field theory are in better agreement with the experimental results.